Determinação de compostos fenólicos, congêneres, contaminantes, carbamato de etila e capacidade antioxidante em cachaças no processo de envelhecimento em barris de diferentes madeiras - Vicente, Cecília Dantas (2011)
The phenolic compounds (gallic acid, vanillic acid, vanillin, syringic acid, syringaldehyde, coumarin and scopoletin), antioxidant capacity, the congeners (acetaldehyde, acetone, furfural, ethyl acetate, n-propanol, isobutanol and isoamyl), contaminants (methanol, sec-butanol and n-butanol), and ethyl carbamate, was determined in cachaças during the aging process. The cachaça were aged in 20 liters barrels, made of nine different woods: jaboty, itauba, timborana, jequitiba, balsamo, courbaril, cerejeira, peroba and oak. The phenolic compounds and furfural were determined by HPLC/UV. The antioxidant capacity was determined using three different methods: the total phenolics by Foulin-Ciocalteu (FC), the inhibition of DPPH radical, and the method of antioxidant power of iron (FRAP). The congeners and contaminants were quantified using GC/MS. The ethyl carbamate was determined through a methodology that makes use of GC/MS with selected ion monitoring (SIM). The botanical origin of the wood’s barrels set phenolic profiles of the samples, which have become more complex, and the concentration of each phenolic compound and antioxidant capacity increased with the aging time. The majority of brazilian woods showed a higher phenolic content and antioxidant capacity than oak. The aged cachaça is a source of exogenous antioxidants, and gallic acid was the main phenolic compound incorporated during the aging process. The cachaça with a higher antioxidant capacity were aged in barrel of balsamo, followed by courbaril, cerejeira, timborana, peroba, jequitiba, oak, itauba and jaboty. The non-aged cachaça showed negligible antioxidant capacity. The aged cachaça in oak showed the similar antioxidant capacity of white wines and whiskeys. A concentration of ethyl acetate, higher alcohols and acetaldehyde increased dramatically with the aging time. The concentration of ethyl carbamate in cachaças remained constant in most of the samples. Through the methodology of principal component analysis (PCA) and hierarchical cluster analysis (HCA) cachaças were grouped according to similarities of their phenolic composition, antioxidant capacity and furfural, forming five groups: group 1 (CNE, itauba, jaboty and oak), group 2 (jequitiba and timborana), group 3 (balsamo and courbaril), group 4 (cerejeira) and group 5 (peroba). From analytical results of congeners in the cachaças could not distinguish them by PCA and HCA. The wood balsamo, followed by timborana, courbaril, jequitiba, oak, itauba and jaboty were the most suitable for aging because had higher antioxidant capacity, and comply with the limits prescribed by law for coumarin, congeners, contaminants and ethyl carbamate. The barrels of cerejeira and peroba were not indicated because during aging showed increased concentrations of coumarin and ethyl carbamate, respectively, with values far above those allowed by law.